The Etiology and Clinical Evaluations of Neonatal Seizures in Kashan, IRAN - TALEBIAN, Ahmad; JAHANGIRI, Mohammad; RABIEE, Mahin Rabiee; MASOUDI ALAVI, Negin; AKBARI, Hossein Akbari; SADAT, Zohreh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Talebian A, Jahangiri M, Rabiee M, Masoudi Alavi N, Akbari H, Sadat Z. The Etiology and Clinical Evaluations of Neonatal Seizures in Kashan, IRAN. Iran J Child Neurol. Spring 2015;9(2):29-41. Abstract Objective Detection of seizure, its etiology, and clinical types is important for guiding therapy. This study was designed to evaluate the etiology and clinical evaluations of neonatal seizures in Kashan, Iran. Materials and Methods The data of 100 hospitalized neonates with a complaint of seizures in Kashan City, from January 2006 to January 2011 were evaluated. The pediatric neurologist made the final diagnosis. The gestational age, neonate admission age, type of delivery, and laboratory and radiological investigations were reviewed from the medical records. The relation of seizure etiology and other variables were compared using the Chi-square test. All the statistical analyses were performed using SPSS (ver 11.5). Results A total of 100 neonates were hospitalized with a diagnosis of seizures. The overall incidence rate of seizures was 2.6 per 1,000 live births. A total of 59% of seizures happened in the first three days of life. The etiologies of seizures were hypoxicischemic encephalopathy (HIE) (36%), hyponatremia (12%), hypoglycemia (11%), intracranial hemorrhage (11%), infections (10%), hypocalcemia (8%), metabolic disorders (7%), the structural anomalies (5%), and hypomagnesaemia (4%). In 23% of neonates, no specific etiology was found and 23% had multiple etiologies. In 45% of neonates, the EEG was not recorded. The type of the seizures were focal-clonic (26%), tonic (25%), multifocal clonic (34%), subtle (11%), and myoclonic (4%). The types of the seizure were unrelated to the paraclinical findings. Conclusion Neonatal seizures are common and HIE was the main cause of seizures in this study. The clinical evaluation of neonatal seizures needs improvement.